Rock Mass Characterization of the Printzsköld and Fabian Orebodies at the Malmberget Mine - Banda, Sraj U. (Luleå tekniska universitet, Geoteknologi, 2013)
Rock mass characterization is usually the first practice required when investigating rock mass responses in mining areas. The ground surface in the Malmberget mine has been affected by subsidence and formation of sinkholes, which have affected many residential areas. As mining progresses to lower levels, caving is expected to occur in the cap rocks of the Printzsköld and Fabian. For optimal planning and operations in the mine, it is therefore necessary to understand the caving mechanism of this area and to investigate the controlling factors in the deformations. This report is a summary of a preliminary rock mass characterization of the Malmberget Mine area, which was aimed at investigating rock mass parameters that will help in the understanding of the caving mechanisms. Diamond core drilling was conducted to obtain rock core for logging. Rock core logging was conducted as well as borehole photography, in which various rock joint orientations were determined. Rock core investigations also revealed zones of weakness due to various phenomena such as weathering, shearing, etc. Laboratory testing of the core samples revealed strength isotropy and high rock mass quality in many areas along the boreholes. Tunnel mapping was carried out only on two production levels of 945 and 970 meters of the Printzsköld orebody. The rock mass has been characterized using the Bieniawski 1989 system of Rock Mass Classification (RMR). The Geological Strength Index was also used to characterize the rock mass in the areas where tunnel mapping took place. Godkänd; 2013; 20131206 (sraban)